Quality assurance: from ancient times to today’s Language Centres - Papadima-Sophocleous, Salomi (My University, 2014)
All domains of our society are currently concerned with quality: quality of services, quality of processes and quality of products. Historically, mechanisms for quality control have existed since the beginning of time. This paper, originating from a workshop on Language Centre Quality Assurance in the ACLES conference (Girona, 2013), takes the reader for a diachronic journey in order to discover the origins of quality assurance and develop an understanding of its presence and importance through the centuries. Then it briefly describes current mechanisms of quality management in different areas. It then focuses on the area of LC quality assurance practices to concentrate on the description of a specific scheme of LC internal quality self-assessment checklist and its piloting in a specific context. Finally it describes a number of external mechanisms for language learning provision. The aim is to acquaint LC practitioners with the notion of LC quality assessment, and LC quality assessment tools in order to assist them in implementing QA in their LC contexts.
Keywords: Quality; Language center